Familial distichiasis - Chowdhury Siti; Chatterjee Shamita (Indian Journal of Plastic Surgery)
Congenital familial distichiasis is a rare condition usually accompanied by other symptoms. Isolated familial distichiasis is rarely heard of. Various modalities of treatment have been tried over the years. We present a case of familial distichiasis spanning over three generations. Our patient was treated with eyelid splitting and follicular extirpation with bipolar cautery. At two years follow-up, there is no recurrence of the distichiatic lashes, with excellent functional and cosmetic result.